Physical characteristics of the handball player - Lidor, R.; Ziv, G. (Handball Sports Medicine, 2018)
Professionals involved in training programs aimed at improving the ability of handball players—coaches, strength and conditioning coaches, physiotherapists, athletic trainers, and sport physicians—should have access to information on the physical aspects of the handball players, so that they can use this information when planning short- and long-term programs for their athletes. In this chapter we (a) review a series of studies (N = 41) on physical characteristics of male (n = 21) and female (n = 20) adult handball players who played at various levels of competition, (b) outline a number of research and measurement concerns associated with the reviewed studies, and (c) propose a number of practical tips for the handball coach and the strength and conditioning coach who work with handball players. Among the research and measurement concerns are the small sample size of the players who participated in the reviewed studies and the limited number of longitudinal studies. Among the practical tips for the practitioner are the use of a systematic collection of data and the use of individual data.